1983
DOI: 10.1007/bf00543805
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and bioavailability of three dyphylline preparations

Abstract: The pharmacokinetics and bioavailability of 3 oral dyphylline preparations, solution (S), regular (R) and sustained release (SR), were studied in 8 healthy subjects (mean age 25 years). A single dose of each preparation, 20 mg X kg-1, was given at one week intervals and multiple serum samples obtained over 24 h. Drug levels were measured by high performance liquid chromatography. No adverse effects were found. The dyphylline half-life for the solution was 2.16 +/- 0.18 h and for the tablet 2.59 +/- 0.56 h. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

1985
1985
2017
2017

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Theobromine is mainly found in cacao and recent evidence shows that it has great potential as an antitussive agent [9]. Theophylline, aminophylline, doxofylline and diprophylline are used in the therapy of bronchial asthma and chronic obstructive pulmonary diseases (COPD) [8,10,11,12,13]. In particular, doxofylline and diprophylline are two novofyllines synthesized to have fewer side effects than other methylxanthines [11,12,13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Theobromine is mainly found in cacao and recent evidence shows that it has great potential as an antitussive agent [9]. Theophylline, aminophylline, doxofylline and diprophylline are used in the therapy of bronchial asthma and chronic obstructive pulmonary diseases (COPD) [8,10,11,12,13]. In particular, doxofylline and diprophylline are two novofyllines synthesized to have fewer side effects than other methylxanthines [11,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Theophylline, aminophylline, doxofylline and diprophylline are used in the therapy of bronchial asthma and chronic obstructive pulmonary diseases (COPD) [8,10,11,12,13]. In particular, doxofylline and diprophylline are two novofyllines synthesized to have fewer side effects than other methylxanthines [11,12,13]. Pentoxifylline is used in the treatment of peripheral vascular diseases and in the management of cerebrovascular insufficiency and diabetic nephropathy [8,10].…”
Section: Introductionmentioning
confidence: 99%
“…The potency of these drugs in zebrafish embryos was also similar to their potency in human and other animal models. Indeed, studies on humans and other vertebrates have shown that etophylline, doxofylline and diprophylline have lesser side effects than other methylxanthines [ 12 , 35 ]. Also, in vivo and in vitro studies have shown theophylline to be more potent than etophylline (7 fold more potent), diprophylline (100 fold more potent) [ 35 ] and doxofylline (10 fold more potent) [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Also, in vivo and in vitro studies have shown theophylline to be more potent than etophylline (7 fold more potent), diprophylline (100 fold more potent) [ 35 ] and doxofylline (10 fold more potent) [ 36 ]. Moreover drugs like doxophylline and diprophylline have fewer side effects as compared to other methylxanthines such as theophylline [ 10 , 12 ]. Overall, our results showed that a single dose of these drugs could be embryotoxic and teratogenic in the zebrafish embryos with potencies comparable to the other higher animal models.…”
Section: Discussionmentioning
confidence: 99%